Short-selling ban and cross-sectoral contagion: evidence from the UK - Mohamad, Azhar; Jaafar, Aziz; Goddard, John (Palgrave MacMillan, 2015)
The UK’s Financial Services Authority (FSA) introduced a ban on the short-selling of specified financial-sector stocks in September 2008. The regulator’s stated objectives were to protect market quality, stabilize the market for financial-sector stocks, and prevent cross-sectoral contagion. We analyse the price, market quality and contagion effects following the imposition of the short-selling ban, and its removal in January 2009. We report evidence consistent with a short-lived overpricing (underpricing) effect immediately after the ban was imposed (lifted). There is evidence of deterioration in market quality while the ban was in force. There is evidence of cross-sectoral contagion from the financial sector to the telecommunication sector immediately prior to the imposition of the ban, but there is no contagion for seven other non-financial sectors. There is no evidence of contagion while the ban was in force. In terms of preventing cross-sectoral contagion, the ban may be seen as a successful governance mechanism in the regulator’s toolbox.